Exclusion, emergence & mobility : a critical socio-spatial assessment of inequality within Hatfield revealing the potential for stations as socio-economic integration hubs - Devenish, Paul (University of Pretoria, 2024)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2023.